The Effects of Partial Immersion Aquatic Intervention on Perceived Physical Competence and Quality of Life in Children With Severe Cerebral Palsy. Issue 2 (May 2021) - Shelef, Niv
Abstract : Background and Purpose: The efficiency of free sitting on function and reaching is restricted in those skills during activities of daily living (ADL) for children with severe cerebral palsy (CP). No longitudinal study so far has examined the stability of perceived competence (PC) and quality-of-life (QOL) domains for this population following water and land intervention environments more than 12 months of follow-up. Case Description: A mixed-methods multiple case design was employed. Five children with severe bilateral spastic CP subtypes (male: n = 4; female: n = 1) aged 10 to 15.4 years (mean = 11.7 years old, SD = 2.1), Gross Motor Function Classification System level IV, participated in the study. Intervention: The innovative "partial immersion approach" (PIA) uses Archimedes' principle to create a restorative therapeutic chair. This therapeutic chair enhances learned functional skills during sitting adaptation in an aquatic environment. It enables the adjustment of weight-bearing by 30 mm, which is transferred to a land environment for practice. Outcomes: All participants experienced adaptation improvement in ADL skills and task movement during free sitting on land and demonstrated quantitative psychological enhancement of PC, with a total increase of 70.60% (161 points) for all participants and a mean increase of 17.65% (40.25 points). Childrenʼs subjective qualitative responses were reinforced by comparing them with proxy objective reports. Each qualitative category that emerged was verified by quantitative data and matched positively and corresponded with major domains across data of QOL instruments. Discussion: Generalization from the findings is limited. The PIA regulates the percentage of weight-bearing from unloading-water toward loading-land and modified the environment for each childʼs needs. This customized environment improved the psychological enhancement of PC and QOL of the participants with severe CP. The successes were retained at the follow-up assessment 12 months after intervention, as participants still exhibited ADL motor acquisition of sitting skills.